Negotiating social boundaries and the management of leisure time within the domestic household : the micropolitics between maids and madams - Erni Nurain Mohd Salleh (2011)
The employment of migrant domestic workers has led to the home becoming a contested space between employers and their domestic workers. With the state’s minimalist intervention over these workers’ working condition and the relegation of discipline to individual employers, social boundaries and private time is negotiated, managed and contested on a daily basis. Based on in-depth interviews with Malay-Muslim employers and their Indonesian Muslim domestic workers, this paper aims to explore how religion affect the strategies and styles of both groups in the domestic politics of space, privacy and religious obligations.